Disability and Attitudes toward It in the Christian Thoughts of St. Augustine and St. Thomas Aquinas - Adam Machowski; Beata Borowska-Beszta (Collectanea Theologica)
Disability as a human condition has aroused the interest of philosophers and theologians from ancient times, through the Middle Ages, to the present day. The article attempts to demonstrate the development and continuity of Christian views on the phenomenon of disability by examining the philosophical and theological thoughts of St. Augustine and St. Thomas Aquinas. The hermeneutical analyses conducted in this article suggest that contrary to the position of theologian Brian Brock, Saint Augustine’s thought concerning disabilities did not focus solely on the category of wonders. Moreover, Augustine’s original openness to disability was not forgotten in the Middle Ages. There is a development in the understanding of disability in the texts of Augustine and Aquinas. It is possible to interpret in this way medieval theological texts referring to disability, as well as texts of Aristotle, which at that time returned to intellectual circulation.